Chain Length of Amphipathic-Type Thioesters Dramatically Affects Reactivity in Aqueous Amidation Reactions with Cysteine Esters - Otomo, Ikumi; Watanabe, Kanna; Kuroda, Chiaki; Kobayashi, Kenichi (SynOpen, 2017)
The reaction of five amphipathic-type thioesters, CH3(CH2)mCOS(CH2)nCOONa (m + n = 12), with cysteine hexyl, butyl, and ethyl esters were studied in aqueous medium. Compounds with the thioester group in close proximity to the carboxylate moiety (m = 10, n = 2) afforded amides in almost quantitative yield, whereas no reaction proceeded by using compounds with the thioester group distant from the carboxylate. In contrast, no clear difference in yield was observed among the five amphipathic-type thioesters upon reaction with valine hexyl ester. The results indicate that the reaction is affected by both the position of the thioester group and the hydrophilic/hydrophobic properties of the amino acid side chain.
Keywords: thioesters; amides; amino acids; micelles; hydrophobic effects